Lenalidomide-Induced High Grade Fever in a Patient with Multiple Myeloma: A Case Report - Ghada, ElGohary; Mohammad, Al Nahedh; Riad, ElFakih (Journal of Clinical Case Reports and Images, 2019)
Lenalidomide is a second generation immunomodulatory agent and a potent analogue of thalidomide that is FDA approved mainly for the treatment of multiple myeloma (MM) and transfusion-dependent anemia due to low or intermediate-1- risk myelodysplastic syndromes (MDS) associated with 5q deletion among other indications. Through its action on the immune system, lenalidomide alters the production of different cytokines ultimately resulting in immune activation against tumors. This immune activation may lead to collateral immune toxicities like fever, angioedema, Stevens-Johnson syndrome, tumor flare and others. Here we report a case of lenalidomide-induced high grade fever in a patient with MM and we summarize the literature about the physiology of such reaction and how to mitigate this adverse event.
Keywords: Lenalidomide; fever; toxicity